2021
DOI: 10.1093/bib/bbab126
|View full text |Cite
|
Sign up to set email alerts
|

Bioinformatics and system biology approaches to identify the diseasome and comorbidities complexities of SARS-CoV-2 infection with the digestive tract disorders

Abstract: Coronavirus Disease 2019 (COVID-19), although most commonly demonstrates respiratory symptoms, but there is a growing set of evidence reporting its correlation with the digestive tract and faeces. Interestingly, recent studies have shown the association of Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) infection with gastrointestinal symptoms in infected patients but any sign of respiratory issues. Moreover, some studies have also shown that the presence of live SARS-CoV-2 virus in the faeces of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 76 publications
0
5
0
Order By: Relevance
“…However, targeting this receptor using natural compounds, e.g., phytoestrogens or estrogens, can prevent SARS-CoV-2 from binding to stressed cells and thus limit infection ( 277 ). Conversely, the IRAK3 hub-high traffic gene is an important inflammatory mediator associated with asthma susceptibility ( 278 , 279 ) and SARS-CoV-2 increases risk of asthma in COVID-19 patients by increasing expression of this gene ( 275 ). Additionally, a network-based study recently suggested the IRAK3 hub-high traffic gene as a potential therapeutic target against COVID-19 ( 280 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, targeting this receptor using natural compounds, e.g., phytoestrogens or estrogens, can prevent SARS-CoV-2 from binding to stressed cells and thus limit infection ( 277 ). Conversely, the IRAK3 hub-high traffic gene is an important inflammatory mediator associated with asthma susceptibility ( 278 , 279 ) and SARS-CoV-2 increases risk of asthma in COVID-19 patients by increasing expression of this gene ( 275 ). Additionally, a network-based study recently suggested the IRAK3 hub-high traffic gene as a potential therapeutic target against COVID-19 ( 280 ).…”
Section: Discussionmentioning
confidence: 99%
“…Bioinformatics and network based approaches provide insight that can be used to identify and analyze the comorbidity complexities (Moni et al, 2019 ; Nashiry A. et al, 2021 ; Nashiry M. A. et al, 2021 ; Islam et al, 2022 ). At the initial stage of this analysis, the datasets required in this work have been identified and collected.…”
Section: Methodsmentioning
confidence: 99%
“…A chemical-protein interaction network is an important research tool for understanding the function of proteins, which is helpful for advancing drug discovery [18,19]. In the aspects of common DEGs as potential drug targets in PSCI, the candidate drugs were identified by using Enrichr based on transcriptome signatures from the DSigDB database [20,21].…”
Section: Identification Of Candidate Drugs and Target-chemical Intera...mentioning
confidence: 99%